Open Access to Judgments: Creative Commons Licences and the Australian Courts - Fitzgerald, A.; Hooper, N.; Foong, Cheryl; Fitzgerald, B. (2012)
Internet technologies have fundamentally changed the way we obtain access to legal documents and information about the law. However, for judgements of courts and tribunals, copyright management and licensing practices have not kept pace with the digital and online technologies which are now ubiquitous in the web 3.0 era. Under the provisions of the copyright Act 1968 and the licensing statements on the Australian courts’ websites, judgements may generally be read online, downloaded, reproduced and printed out for personal, non-commercial use or ‘in house’ use by an organisation. However, beyond these permitted acts, the extent to which judgments can be copies and distributed in digital form online remains unclear. Open content licences (in particular, the Creative Commons (CC) licences) offer an effective mechanism for managing copyright in judgments in a manner that supports their wide public dissemination and reuse while also protecting their integrity and accuracy.